Avaliação de hemoparasitos e ectoparasitos em quatis (Procyonidae: Nasua nasua) no parque das Mangabeiras, Belo Horizonte, Minas Gerais - Letícia Gracielle Tôrres de Miranda Estevam (2017)
The wild animals have been recognized as potential reservoirs of vector-borne pathogens. The proximity of these animals with urban areas increases the need to know which pathogens are these and if they can infect domestic animals and human beings. In the park Parque Municipal das Mangabeiras, Belo Horizonte, Minas Gerais, there are coatis of the species Nasua nasua that live very close to the urban areas, which is mainly composed by residents and domestic animals from Vila Marçola, a neighborhood adjacent to the park. Accordingly, the objective of this study was to detect, through molecular and direct methods, the presence of ectoparasites and hemoparasites that might be infecting the coatis from Parque das Mangabeiras. There were found species of ticks (Ambyomma sp., A. ovale, A. sculptum and Rhipicephalus microplus), louses (Neotrichodectes pallidus) and fleas (Rhopallopsyllus lutzi lutzi and Ctenocephalides felis felis) and there were detected infections by Hepatozoon sp., Babesia sp., Sarcocystis neurona, Trypanosoma evansi and microfilariae. The samples were tested negative for the primers used for the detection of T. cruzi, E. canis/A. platys e Ehrlichia granulocitica, showing that some of these zoonotic agents are not infecting the coatis, though other parasites still must be researched. Consequently, it was possible to demonstrate that there is a wide variety of pathogens infecting the coatis in the park. These are parasites that can infect a wide diversity of animals, both wild and domestic, showing the need of active surveillance of the wild animals that live in the park, and of the domestic animals that live in the surrounding areas.